Muscular performance analysis in “cross” modalities: comparison between “AMRAP,” “EMOM” and “RFT” configurations - Barba-Ruíz, Manuel; Hermosilla-Perona, Francisco; Heredia-Elvar, Juan Ramon; Gómez-González, Noelia; Da Silva-Grigoletto, Marzo Edir; Muriarte-Solana, Diego (Frontiers in Physiology, 2024)
In recent years, a surge of interest in high-intensity training methods, associated with "cross" modalities has emerged as a promising approach for improving performance and overall health. Therefore, the main aim of this study was to compare the acute effects on heart rate, mean propulsive velocity and intra and inter-set velocity loss in "Cross" modalities.Materials and methods: Twelve athletes, 10 men's and 2 women's (age: 31.5 ± 6.74 years; height: 174.17 ± 6.05 cm; weight: 75.34 ± 7.16 kg) with at least 1 year of experience in "cross" training. The participants performed three different "cross" modalities, Rounds for Time (RFT), Every Minute on the Minute (EMOM) and As Many Rounds As Possible (AMRAP) across three separate days. In each modality participants carried out 10 repetitions of squat, pull-ups, and shoulder press with difference rates of work-rest. Mean propulsive velocity (MPV) and heart rate (HR) were recorded and analysed for each athlete. Repeated measures one-way ANOVA and repeated measures two-way ANOVA were performed to analyse the differences between modalities and subjects. Besides, a Bonferroni post-hoc analysis was carried out to assess the differences between modalities in each subject.Results: Significant differences in MPV were observed among the modalities. The comparisons between RFT and AMRAP, as well as EMOM and AMRAP, revealed lower MPV in the AMRAP modality (p<0.01). RFT exhibited the greatest intra-set velocity loss, while EMOM showed the least, with significant distinctions (p<0.01) between them. Furthermore, significant differences in the HR results were noted among all modalities (p<0.05).Findings consistently identify the AMRAP modality as having the lowest MPV values due to its prolonged duration, promoting self-regulated tempo for optimal performance and technique, while the RFT modality exhibits higher fatigue and intra-set MPV losses. These insights into propulsive velocity, intensity, fatigue, and pacing across various "Cross" modalities provide valuable guidance for athletes and trainers seeking to enhance their exercise programs.